2017
DOI: 10.1371/journal.pone.0169790
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Molecular Clockwork of the Oyster Crassostrea gigas

Abstract: Molecular clock system constitutes the origin of biological rhythms that allow organisms to anticipate cyclic environmental changes and adapt their behavior and physiology. Components of the molecular clock are largely conserved across a broad range of species but appreciable diversity in clock structure and function is also present especially in invertebrates. The present work aimed at identify and characterize molecular clockwork components in relationship with the monitoring of valve activity behavior in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 54 publications
1
30
0
Order By: Relevance
“…4). This mirrors the situation in other lophotrochozoans investigated to date (Arendt et al, 2004; Zantke et al, 2013; Bao et al, 2017; Perrigault and Tran, 2017), as well as in crustaceans (Zhang et al, 2013) and some insects (Rubin et al, 2006). …”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…4). This mirrors the situation in other lophotrochozoans investigated to date (Arendt et al, 2004; Zantke et al, 2013; Bao et al, 2017; Perrigault and Tran, 2017), as well as in crustaceans (Zhang et al, 2013) and some insects (Rubin et al, 2006). …”
Section: Discussionsupporting
confidence: 78%
“…Lophotrochozoans, such as molluscs, represent an animal clade that can potentially shed some light on this question. Recent research on the oyster Crassostrea gigas found that the bivalve circadian clock may be intermediate to that seen in mammals and Drosophila , with both TIMELESS and NPCRY possibly acting as transcriptional repressors and PCRY providing light input to the clock (Perrigault and Tran, 2017). This is actually similar to the proposed clock mechanism in some non-drosopholid insects, such as butterflies (Zhu et al, 2008), and the chelicerate Limulus (horseshoe crab) (Chesmore et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the complete genome of this species was published [20]. Moreover, circadian clock genes and the cyclic transcriptome have been studied in C. gigas [21,22], making it an ideal candidate to investigate molecular clockwork and test hypotheses to explain circatidal rhythmicity.…”
Section: Introductionmentioning
confidence: 99%